Firm profits and government activity: An empirical investigation - Petar Jolakoski; Branimir Jovanović; Joana Madjoska; Viktor Stojkoski; Dragan Tevdovski (The Vienna Institute for International Economic Studies (wiiw), 2021)
If firm profits rise to a level far above than what would have been earned in a competitive economy, this might give the firms market power, which might in turn influence the activity of the government. In this paper, we perform a detailed empirical study on the potential effects of firm profits and markups on government size and effectiveness. Using data on 30 European countries for a period of 17 years and an instrumental variables approach, we find that there exists a robust relationship between firm gains and the activity of the state, in the sense that higher firm profits reduce government size and effectiveness. Even in a group of developed countries, such as the European countries, firm power may affect state activity.
Keywords: C23; H11; H50; 330; firm profits; government size; government effectiveness